2018
DOI: 10.2174/1381612824666180131120859
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Atrial Fibrillation and Cardiac Surgery: Current Medical and Invasive Approaches for the Treatment of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is a cardiac dysrhythmia commonly seen in clinical practice especially after cardiac surgery. It is associated with increased morbidity and mortality for the patients. The pathogenesis of AF is not exactly understood yet, but there is growing data about the relationship between AF and inflammation. Cardiac surgery itself is a big source for inflammation. It causes major surgical trauma, ischemia/reperfusion injury, hypothermia, low arterial pressure, and the equipment of cardiopulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Coronary artery disease, valvular heart disease, and heart failure are associated with high inflammatory load and possess high atrial fibrillation risk. After surgery, the systemic inflammatory response is induced, resulting in higher atrial fibrillation risk, especially on the second and third days (6).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease, valvular heart disease, and heart failure are associated with high inflammatory load and possess high atrial fibrillation risk. After surgery, the systemic inflammatory response is induced, resulting in higher atrial fibrillation risk, especially on the second and third days (6).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that interleukin (IL) family members serve critical roles in the occurrence and progression of AF (5). A previous study reported that polymorphism of the IL-1 receptor antagonist gene allele 2 resulted in a poorly restricted inflammatory response and promoted the presence of lone AF (6).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, based on its original purpose, CytoSorb ® also offers the possibility to treat hyperinflammation, which inevitably occurs due to the surgical trauma [ 16 ]. As the adsorber also eliminates other deleterious substances, it appears plausible that it would be particularly suitable for patients with increased cytokine levels as well as infections and infarctions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%